Investigate the efficiency of energy recovery ventilator in HVAC system - Chong, Chee Yee (2016)
Air-conditioning is widely used in Singapore with its hot and humid climate. The energy consumed by the Heating, Ventilation and Air-Conditioning (HVAC) typically accounts for approximately 50% [1] of the total energy consumption in a building. With the amount of buildings being fitted with air-conditioning system in Singapore, any opportunity of improving the energy efficiency is being looked into. In an air-conditioning system, the chiller took up major proportion of the energy consumption, with the rest taken up by fans, pumps and cooling towers. This project will study the feasibility of using a membrane-based type of energy recovery ventilator (ERV) in the air-conditioning system for hot and humid climate condition to reduce the cooling load of the chiller and reduce the overall energy consumption. Indoor air quality is placed into consideration as well because good indoor air quality will lead to increased productivity and maintain good health conditions of the occupants since a substantial amount of time is spent in these premises. For this project, EnergyPlus software is used for the simulation of the cooling load required and for the comparison of energy consumption between different configurations of the cooling system. There will be three different configurations of the simulations and the results would be compared with each other so as to check for the feasibility of its application in Singapore’s climate as well as finding out the best configurations.